Energetic mitochondrial failing in vitiligo and possible rescue by cardiolipin. Issue 1 (December 2017) - Dell'Anna, Maria; Ottaviani, Monica; Kovacs, Daniela; Mirabilii, Simone; Brown, David; Cota, Carlo; Migliano, Emilia; Bastonini, Emanuela; Bellei, Barbara; Cardinali, Giorgia; Ricciardi, Maria; Tafuri, Agostino; et al.
Abstract Vitiligo is characterized by death or functional defects of epidermal melanocytes through still controversial pathogenic process. Previously, we showed that mitochondria-driven pre-senescent phenotype diminishes the capability of vitiligo melanocytes to cope with stressful stimuli. In the current study, we investigated markers of mitochondrial energy metabolism including the PGC1a axis, and then we determined the index of mitochondrial impairment using a cytomic approach. We found in cultured epidermal vitiligo melanocytes, compared to healthy ones, low ATP, increased proton leakage, and altered expression of several glycolytic enzymes (hexokinase II, pyruvic dehydrogenase kinase 1 and pyruvic kinase M2), We suggest that the low ATP production may be sufficient in steady-state conditions but it is unable to cover further needs. We also found in vitiligo melanocyrtes hyper-activation of the PGC1α axis, finalized to counteract the energy defect. Cytomic analysis, supported by MitoTracker Red pattern andex-vivo immunohistochemistry, suggested an increased mitochondrial mass, possibly useful to ensure the essential ATP level. Finally, pharmacological cardiolipin stabilization reverted the energetic impairment, confirming the initial mitochondrial role. In conclusion, we report new insight in the pathogenetic mechanism of viitligo and indicate that the mitochondrial failure rescue by cardiolipin manipulation may be a new intriguing target in treatment development.